Utopia in the world political-legal theory and practice - Pylypenko, Denis (Utopía y Praxis Latinoamericana)
The history of political and legal thought is inextricably linked with multiform approaches to the study of the essence of the state as a multi-element category. Scientists tried to find ways and means of creating a society that could become a prototype and model of an etalon union of people leading to the universal happiness and balance of interests of each individual in it. In the search for the best or best form of the state, the concepts of difficult to execute and sometimes even illusory forms of social management were forming, which were defined as utopian projects.